Dose-response relationship of neuromuscular training for injury prevention in youth athletes: a meta-analysis - Steib, Simon; Rahlf, Anna L.; Pfeifer, Klaus; Zech, Astrid (Frontiers in physiology, 2017)
Background: Youth athletes with intensive sports participation are at an increased risk of sustaining injuries. Neuromuscular training programs reduce sports-related injury risk in this population, however, the dose-response relationship is largely unknown. Thus, the aim of this meta-analysis was to identify the optimal frequency, volume, duration, and period of neuromuscular training to prevent injuries in youth athletes.Methods: Computerized database searches (PubMed, Scopus, SPORTDiscus, The Cochrane Library, PEDro) were conducted in January 2017, with search terms related to youth sports, neuromuscular training, and injury prevention. Eligible trials (i) evaluated a neuromuscular training program; (ii) included youth athletes of 21 years or younger; (iii) had an analytical design (RCTs, quasi-experimental, cohort studies); (iv) contained original data; (v) and provided injury data. Two reviewers independently extracted data and assessed quality of eligible studies. Injury rate ratios (IRRs) for lower extremity injuries were pooled meta-analytically, and moderator analyses examined the effect of training frequency, duration, volume, and period.Results: Data from 16 trials yielded an overall risk reduction of 42% with neuromuscular training (IRR = 0.58, 95%CI 0.47-0.72). Training frequencies of two (IRR = 0.50; 95%CI 0.29-0.86) or three times (IRR = 0.40; 95%CI 0.31-0.53) per week revealed the largest risk reduction, and a weekly training volume of more than 30 min tended to be more effective compared to lower volumes. Programs with 10-15 min (IRR = 0.55; 95%CI 0.42-0.72) session duration produced effects comparable to those with longer session duration (IRR = 0.60; 95%CI 0.46-0.76). Interventions lasting more than 6 months were not superior to shorter programs.Conclusion: This meta-analysis revealed that NMT performed in short bouts of 10-15 min, two to three times per week, with a weekly training volume of 30-60 min had the largest preventive effect for lower extremity injuries in youth athletes. These effects can be achieved within 20-60 sessions and training periods of <6 months. The present results are derived from a relatively small number of studies with heterogeneous methodological quality and should be treated with caution.The study was a priori registered at PROSPERO (CRD42016053473).
Gesehen am 13.07.2022